Validity of self‐reported anthropometrics in Arabic‐speaking adults in Australia. (2nd January 2020) - Arjunan, Punitha; Kovai, Vilas; Jalaludin, Bin; Rooney, Janelle
Abstract: Issue addressed: Body mass index (BMI) is generally accepted as a useful measurement for monitoring risk factors in adults. Although self‐reported anthropometric measurements are deemed to be more cost‐effective, its accuracy has been debated. While BMI based on self‐reported measures may have to be relied on, accuracy of reporting such measures among culturally and linguistically diverse groups is unknown. Methods: Face‐to‐face surveys were conducted among 272 adults of Arabic‐speaking backgrounds living in south western Sydney using non‐probability sampling to collect data for directly measured and self‐reported BMI. Agreement between both measures was determined by the Cohen's kappa coefficient analyses. The Wilcoxon matched‐pairs signed‐ranks and Mann‐Whitney U tests were used to compare the differences in median values between both measures. The Bland‐Altman analysis was conducted to identify the limits of agreement between both measurements. Results: There was substantial agreement between both self‐reported and directly measured data (kappa = 0.70). Significant small median differences were found between both direct and self‐reported overall BMI measure (27.58 vs 27.34; P  < .0001) with a significantly greater median difference for females compared to males (0.76 vs 0.38 kg/m 2 ; P  = .05). However, the 95% limits of agreement were moderately large for BMI (−5.1 and 6.4). Conclusion: Self‐reported data for height and weight are generally appropriate for calculating BMI for health promotion interventions among adults from Arabic‐speaking backgrounds but should be used cautiously when assessing BMI status at the individual level. So what?: When limited resources are available for accomplishing health promotion interventions, self‐reporting measures may be used as a proxy for assessing BMI. Summary: Although self‐reported anthropometric measurements are deemed to be more cost‐effective in calculating BMI, its accuracy among people of Arabic‐speaking background is unknown. Using face‐to‐face surveys among adults, this study shows that self‐reported height and weight are generally appropriate to assess BMI status among adults from Arabic‐speaking backgrounds.